RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI KEUANGAN PENGEMBANG PROPERTI PADA PT DUA DAYA SAKTI - Pratama, Harits Yulianta; Wurijanto, Tutut; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT Dua Daya Sakti is a company engaged in the development of property, especially housing and home stores. One of the mission that must be achieved by the company is to provide the best service and prioritize customer satisfaction by always trying to finish the job on time. Every operational and development activity, the financial department must know each income and expense of each department for the recording of the company's cash flow. Every financial transaction will be recorded in the data processing application that is Microsoft Excel. The amount of data that needs to be processed and not integrated data on the operational departments and finance departments, resulting in the availability of data required for the preparation of financial statements has not been maximized. Based on these problems, there is a gap between one of the company's mission to be achieved with the current condition of the company. The solution offered is to utilize information technology that is making financial administration information system. The test results show that this information system can produce financial reports from transaction processing system.